Deletion of the Response Regulator PhoP Accelerates the Formation of Aerial Mycelium and Spores in Actinosynnema pretiosum - Zhang, Peipei; Zhang, Kunyu; Liu, Yayu; Fu, Jiafang; Zong, Gongli; Ma, Xin; Cao, Guangxiang (Frontiers in Microbiology, 2022)
PhoPR is an important two-component signal transduction system (TCS) for microorganisms to sense and respond to phosphate limitation. Although the response regulator PhoP controls morphological development and secondary metabolism in various Streptomyces species, the function of PhoP in Actinosynnema pretiosum remains unclear. In this study, we showed that PhoP significantly represses the morphological development of the A. pretiosum X47 strain. Production of aerial mycelium and spore formation occurred much earlier in the ΔphoP strain than in X47 during growth on ISP2 medium. Transcription analysis indicated that 222 genes were differentially expressed in ∆phoP compared to strain X47. Chemotaxis genes (cheA, cheW, cheX and cheY); flagellum biosynthesis and motility genes (flgBCDGKLN, flaD, fliD-R, motA and swrD) and differentiation genes (whiB and ssgB) were significantly up-regulated in ∆phoP. Gel-shift analysis indicated that PhoP binds to the promoters of flgB, flaD and ssgB genes, and PHO box-like motif with the 8-bp conserved sequence GTTCACGC were identified. The transcription of phoP/phoR of X47 strain were induced at low phosphate concentration. Our results demonstrate that PhoP is a negative regulator that controls the morphological development of A. pretiosum X47 by repressing the transcription of differentiation genes.